2016
DOI: 10.1227/neu.0000000000001419
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of Lumbar Decompression Adjacent to Instrumented Segments

Abstract: MI, minimally invasive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 42 publications
1
10
0
1
Order By: Relevance
“…Resection of facet joints destabilizes spinal segments proportional to the amount of joint removed (37)(38)(39). Moreover, removal of midline structures further contributes to segmental destabilization (38,40). In order to minimize post decompression instability and subsequent need for arthrodesis surgery, several minimally invasive technique aiming to preserve facet joint function and midline structures have been developed.…”
Section: Discussionmentioning
confidence: 99%
“…Resection of facet joints destabilizes spinal segments proportional to the amount of joint removed (37)(38)(39). Moreover, removal of midline structures further contributes to segmental destabilization (38,40). In order to minimize post decompression instability and subsequent need for arthrodesis surgery, several minimally invasive technique aiming to preserve facet joint function and midline structures have been developed.…”
Section: Discussionmentioning
confidence: 99%
“…Stability describes the ability to maintain equilibrium despite the presence of kinematic and/or control disturbances. The mechanical stability of lumbar spine is considered an important factor [ 14 ] for ensuring the balance and posture required for normal daily activities such as walking, running, flexion, and extension [ 15 ]. Particularly, lumbar spine instability determines an increased risk of recurrent lumbar spine disc herniation, which, subsequently, often leads to disorders in the lower limbs loading, impairs proprioception and deteriorates postural stability [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our biomechanical study revealed that if decompressing a segment adjacent to a simultaneously performed fusion, it is crucial to preserve both facet joints in order to maintain stability. The findings of this study suggested that a mono-segmental MIS-TLIF combined with an adjacent MIS-tubular decompression is superior to a mono-segmental MIS-TLIF with adjacent level open laminectomy (14).…”
Section: Review Of Techniquesmentioning
confidence: 70%
“…On the other hand, a decompression without fusion when performed adjacent to a fused level may be associated with instability and failure (11)(12)(13). In order to assess the biomechanical stability of a simultaneously performed single level MIS-TLIF and decompression without fusion of the adjacent stenotic segment, our group recently performed a biomechanical cadaver study (14). The findings of this particular study suggest that, if done in a minimally invasive fashion, a unilateral laminotomy for bilateral decompression (ULBD) of the adjacent segment causes significantly less motion than a traditional open laminectomy.…”
Section: Review Of Techniquesmentioning
confidence: 99%